Advances in understanding the interplay between dietary practices, body composition, and sports performance in athletes - Martín-Rodríguez, A.; Belinchón-deMiguel, P.; Rubio-Zarapuz, A.; Tornero-Aguilera, J. F.; Martínez-Guardado, I.; Villanueva-Tobaldo, C. V.; Clemente-Suárez, V. J. (Nutrients, 2024)
The dietary practices of athletes play a crucial role in shaping their body composition, influencing sports performance, training adaptations, and overall health. However, despite the widely acknowledged significance of dietary intake in athletic success, there exists a gap in our understanding of the intricate relationships between nutrition, body composition, and performance. Furthermore, emerging evidence suggests that many athletes fail to adopt optimal nutritional practices, which can impede their potential achievements. In response, this Special Issue seeks to gather research papers that delve into athletes` dietary practices and their potential impacts on body composition and sports performance. Additionally, studies focusing on interventions aimed at optimizing dietary habits are encouraged. This paper outlines the key aspects and points that will be developed in the ensuing articles of this Special Issue.